2009
DOI: 10.3136/fstr.15.367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modified Atmosphere and Vacuum Packaging on the Physicochemical, Microbiological, Sensory and Textural Properties of Crottin de Chavignol Cheese

Abstract: In this work, it was aimed to determine the effect of packaging technique on some quality properties of "Crottin de Chavignol" type goat cheese packaged under vacuum (VP) and modified atmosphere (MAP) (%20 CO 2 + %80 N 2 ) during storage at + 4℃ and also to compare these two packaging techniques to be able determine the more suitable packaging technique for "Crottin de Chavignol" type goat cheese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The total number of aerobic mesophilic bacteria (data not shown) did not exceed 3.27 log cfu g -1 which was the highest value recorded after 9 days of cold storage of the sample BT-01. In comparison to our previous study with the same type of cheese (Barukčić et al, 2020), as well as to the results of other authors (Dermiki et al,2008;Del Nobile et al, 2009;Kizilirmak Esmer et al, 2009) who obtained values up to 7 log cfu g -1 , the values determined in the present study were much lower. Despite that, in most of the samples either other categories of inspected microorganisms increased (Figures 2a-c) above the recommended limits or the sensory properties were unsatisfactory after 9 days of storage, which as regarded as the end of their shelf life.…”
Section: Microbiological Analyses Of Fresh Cheesesupporting
confidence: 73%
See 1 more Smart Citation
“…The total number of aerobic mesophilic bacteria (data not shown) did not exceed 3.27 log cfu g -1 which was the highest value recorded after 9 days of cold storage of the sample BT-01. In comparison to our previous study with the same type of cheese (Barukčić et al, 2020), as well as to the results of other authors (Dermiki et al,2008;Del Nobile et al, 2009;Kizilirmak Esmer et al, 2009) who obtained values up to 7 log cfu g -1 , the values determined in the present study were much lower. Despite that, in most of the samples either other categories of inspected microorganisms increased (Figures 2a-c) above the recommended limits or the sensory properties were unsatisfactory after 9 days of storage, which as regarded as the end of their shelf life.…”
Section: Microbiological Analyses Of Fresh Cheesesupporting
confidence: 73%
“…The pH drop in the cheese was rather caused by the production of lactic acid during the fermentation, as well as by the formation of carbonic acid arising from CO2 dissolving in acidic media. The increase in pH value can also be a consequence of the activity of yeasts and moulds that metabolize alkaline components into lactic acid increasing thereby the total pH value in fresh cheese (Kizilirmak Esmer et al, 2009).…”
Section: Cheese Yield and Chemical Composition Of Cheesementioning
confidence: 99%
“…Under anaerobic conditions, when the amount of oxygen is limited, the microbiota established during the storage of V cheeses will be different from that in N cheeses [ 26 ]. This trend has already been demonstrated in other cheeses such as Cameros [ 28 ], Parmigiano Reggiano [ 29 ], Provolone [ 30 , 38 ], Saloio [ 17 ], Crottin de Chavignol [ 39 ] and Arzúa-Ulloa [ 31 ]. It therefore seems that chilled storage (4 °C) will slow down the enzymatic action, which is consistent with the low intensity of proteolytic reactions observed at this stage.…”
Section: Resultsmentioning
confidence: 58%
“…Air-packaged cheeses were the lowest rated for flavour and presented defects in the paste appearance at the end. Indeed, it has been reported that CO 2 concentrations below 20% do not inhibit the growth of moulds [21,47]. Short storage times have been described for cheeses kept in air on account of mould growth [22,37,48].…”
Section: Sensory Analysismentioning
confidence: 99%